2007
DOI: 10.1590/s0034-72992007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Processo de adaptação de próteses auditivas em usuários atendidos em uma instituição pública federal: parte II: resultados dos questionários de auto-avaliação

Abstract: An efficient rehabilitation must be able to reduce impairment effects over the auditory and communication skills of individuals and promote psychosocial well being. Aims: check the feasibility of using self-assessment questionnaires and compare the results achieved by hearing aid fitting in users from a federal public institution, with and without complaints related to hearing amplification characteristics. Materials and Methods: 25 individuals, from 13 to 77 years of age, users of hearing aids. The HHIE-S/ HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
3
10
0
6
Order By: Relevance
“…The Italian version of the HHIA kept the validity and reliability of the original version, being considered of high relevance in order to establish the non-auditory symptoms of the hearing impaired from that country 7 . The HHIA questionnaire was translated into Brazilian Portuguese 8 and has been used both in the audiology clinic as well as in research in order to quantify the handicap of a population, to assess the benefits of using the ISAD or that of intervention programs for people with noise-induced hearing loss [8][9][10][11][12] . Nonetheless, data on the validity and reliability of the HHIA translated into Brazilian Portuguese has not been reported in the literature, and this is a limiting factor in regards of the usefulness of the instrument for use in research or to document clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The Italian version of the HHIA kept the validity and reliability of the original version, being considered of high relevance in order to establish the non-auditory symptoms of the hearing impaired from that country 7 . The HHIA questionnaire was translated into Brazilian Portuguese 8 and has been used both in the audiology clinic as well as in research in order to quantify the handicap of a population, to assess the benefits of using the ISAD or that of intervention programs for people with noise-induced hearing loss [8][9][10][11][12] . Nonetheless, data on the validity and reliability of the HHIA translated into Brazilian Portuguese has not been reported in the literature, and this is a limiting factor in regards of the usefulness of the instrument for use in research or to document clinical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Freitas and Costa (2007) 11 , the self-evaluation questionnaires are effective tools to measure the difficulties caused by hearing impairment. Some of these difficulties can be identified by assessing the self-perception of hearing impaired about their communication needs, allowing the establishment of targets for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…comprehends since guidance and programming made up to the effective use of such by the patient, is capable of generating auditory benefits, minimizing the difficulties caused by the hearing loss 11 . The same has been cited by other authors 12 , who suggested that the professionals working in the field of Audiology must know the difficulties of each patient.…”
Section: In the Elderly Groupmentioning
confidence: 99%
“…Há os que afirmam que a estrutura de grupo 25 interfere na melhora da comunicação e nas habilidades auditivas de reconhecimento de fala de adultos usuários de implante coclear. Outros trabalhos 26,27 também corroboram nossos dados, ao afirmar que o questionário IOH-HA é uma ferramenta simples e de fácil aplicação e excelente para detectar diferenças quando se compara duas situações distintas.…”
Section: Discussionunclassified